MANUSIA UTAMA PERSPEKTIF SVAMI VIVEKANANDA - Luh Kartika Dewi; Putu Eka Arsadi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
This article describes how the ideal human concept according to Svami Vivekananda. Although there has been much research on humans, but there are many problems that remain unanswered because of the complexity of the humans problem itself. Especially if it is associated with Hindu teachings, wich is now called the Kaliyuga era. In this era, human in general have not succeeded in realizing it ideal character or perfect human because of the decline in the quality of human character that characterizes the times of Kaliyuga. As a being who has a conscience, humans should be able to sort out and choose good ones in carrying out their lives for the sake of the realization of the goal of human life itself and become the main human being. Hindu religious teachings provide solutions in the form of concepts from the main human being that can be a benchmark for the people, one of them is the main human concept of one of the hindu spiritual leaders namely Svami Vivekananda. With the human concept of Svami Vivekanda, it is expected that Hindus in particular can make the concept a guideline in behaving in order to realizing the ultimate and useful Hindu people for live.